Economia compartilhada na saúde: atratividade do mercado para plataformas de agendamento de consultas médicas - Espino, Gilmara Pereira (2018)
The assessment of a market attractiveness is critical when deciding to invest in a new company or business segment. Specific sectors require specific knowledge, not always perceived in feasibility studies conducted on generalist assumptions. Recently, a sudden expansion of sharing economy companies offering online scheduling medical platforms has raised the issue of this particular market. This study presents the social, economic and technological factors that explain the increase of competitors and also explore the existing market barriers that makes the diffusion of this kind of platform so difficult in Brazil. More than understanding the phenomenon, the outcome presents a current overview about the Brazilian health environment and the users’ perception. Therefore, it’s a knowledge that can be applied to feasibility studies of other products or services that wish to compete in the Health sector. The analysis based on evidence from researched literature, interviews, survey and observation (hidden customer) concludes in direction to the lessen of interest by investments in companies that act exclusively on online-scheduling medical platforms based on sharing economy; and point to a more concentrated market with fewer small competitors who need to diversify their products and services in order to keep themselves competitive.